PEMBATASAN PNS DALAM KEGIATAN USAHA SWASTA1 - Rudiat Komara2 (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2007)
Government Regulation No 6 Year 1974 restricts civil servants from private and ownbusinesses. This regulation intends that civil servants fully commit to accomplishing their jobs. In addition, civil servants should not create negative image due to their irrespective manners. Despite the regulation, there are still many civil servants involved in their own profitoriented businesses. This condition is believed to reduce civil servants’ profesionalism, especially in terms of competency, discipline, and ethics. Even so, the regulation does not seem to impede civil servants from getting engaged in their own profit-oriented businesses due to their current welfare status regarded as low.